Karakteristik Pedagang Kaki Lima dan Persepsi Pengunjung di Kawasan Kota Lama Makassar - Muthya Rusli Gailea; Arifuddin Akil; Isfa Sastrawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2014)
The uncontrolled of growth and development of street vendors in town decreases environment quality and physical appereance of urban perform. The old city district of Makassar is the tourism district which the most popular district visited by the tourists. It is proved by the existence of Fort Rotterdam as the historical tourism building and Losari Beach Bridge as the icon of Makassar City. The street vendors notice that the district is a potential to looking for some advantages. That is the reason why the street vendor tooke place in The Old City District of Makassar. The literature reviews notice the characteristic of street vendors, the spreading pattern of street vendor and the visitor‟s perception in three research sub-districts (Bulogading, Maloku, and Losari Sub[1]district). The spatial analysis describes the spreading pattern of street vendor which was observed by the kind of commerce, the location of commerce and the service time. Meanwhile, the qualitative description analysis and the quantitative analysis are used to describe the existing condition of street vendor, to identificate the character of street vendors and to identificate the visitor‟s perception. The samples were collected randomly (proportional stratified random sampling).The analysis result reveals about the lively visiting level is the main factor which causing the appeareance of street vendors in the old city district of Makassar. The street vendors which have cluster spreading pattern (focus aglomeration) are kid‟s toys store and haberdasherry. Furthermore, the street vendors that have stretch spreading pattern (linier) are mixture type, individual service and printed matter. Meanwhile, the half amount of the street vendors like food and beverage merchant have stretch spreading and the rest has cluster spreading pattern. The indicators such as cheap, delicious and the quality of food become the main reason for people to visit the street vendors. The effective arrangements of the street vendors are providing street vendors pocket, providing park facility and controlling security. Those will be able to minimize the problems that could occure in the future. However, the old city district of Makassar is not only as trading facility support but also as tourism facility support.